A graphene copper alloy and its preparation method and application
By controlling the composition and structure of graphene copper alloy, a good bonding interface is formed, which solves the oxidation problem and the problem of excessive thermal expansion coefficient in copper wire bonding technology, and achieves excellent oxidation resistance and low oxidation performance of graphene copper alloy. Coefficient of thermal expansion and high conductivity.
Patent Information
- Application Number
- CN202411412166.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-10-11
AI Technical Summary
The existing copper wire bonding technology is prone to oxidation in actual application, resulting in failure problems such as non-stick welding, insufficient tensile strength, and welding injuries. At the same time, the large thermal expansion coefficient affects the service life.
By controlling the graphene content, layer number and oxygen content in the graphene copper alloy, a good bonding interface is formed to avoid graphene agglomeration, and graphite with low thermal expansion coefficient, excellent antioxidant properties, conductive properties and mechanical properties are prepared. Elenocopper alloy.
The low thermal expansion coefficient of graphene copper alloy is achieved, the oxidation resistance and conductivity are improved, the mechanical properties are enhanced, and the service life of the bonding wire is extended.
Smart Images

Figure CN118910464B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of copper alloys, and in particular relates to a graphene copper alloy and a preparation method and application thereof. Background Art
[0002] The thermal conductivity of graphene material is 5000W / (mk), which is more than 10 times that of common metals. It has excellent electrical conductivity and good mechanical and optical properties. In addition, as a two-dimensional planar material, graphene has a stable structure and good corrosion resistance. In recent years, the preparation process of graphene materials has gradually matured, and graphene / copper composite materials are also a research focus. However, current research mainly focuses on improving the performance of graphene and copper matrix, and there is little research on the practical application of graphene copper materials, especially in semiconductor bonding wires.
[0003] The electrode terminals of IGBT chips, the electrode terminals of IGBT chips and diode chips, and the electrode terminals of chips and insulating linings are generally electrically connected through wire bonding technology. The chips are interconnected through bonding wires to form a loop. Wire bonding is one of the main ways to achieve electrical interconnection inside IGBT power devices. With the rapid development of manufacturing technology, many metal bonding wires are widely used in IGBT power module interconnection technology.
[0004] At present, commonly used bonding wires include aluminum wire, gold wire, silver wire, copper wire, aluminum strip, copper sheet and aluminum-clad copper wire. Copper wire has lower resistivity than aluminum wire, better electrical conductivity, higher thermal conductivity than aluminum wire and better heat dissipation performance. Most power modules now pursue small size, high power density and fast heat dissipation, and copper wire bonding technology has been widely used.
[0005] However, compared with gold wire, copper wire is easy to oxidize during the bonding process. Once the solder ball is oxidized, the copper wire will not be able to bond properly with the chip electrode, which will cause failure problems such as non-stick welding, insufficient tensile strength, and welding damage. In addition, the thermal expansion coefficient of the bonding wire is one of the key factors affecting the service life. Once the expansion coefficient is too large, the life of the bonding point will drop sharply under the long-term action of current heating.
[0006] To solve the problem of surface oxidation of bonding copper wires, silver plating is mainly used to isolate the air. However, the silver plating process is complicated and costly, and the wire is easily distorted during the bonding process. In addition, silver has a high hardness and is easy to damage the chip during bonding, resulting in craters and cracks. Patent document CN107195608A uses a vacuum casting method to add 0.1% of silver and rare earth elements by total weight and then draw the wire to the finished product specifications. It has extremely high requirements for raw materials, requiring 6N high-purity copper and 5N high-purity silver and rare earth, which makes it difficult to achieve mass production. The thermal expansion coefficient is an intrinsic property of the material, and very few patents involve it.
[0007] Patent document CN108149046A discloses a high-strength, high-conductivity graphene / copper nanocomposite material and its preparation method and application. The preparation method includes: using a Cu-Mn binary alloy plate or a Cu-Ni binary alloy plate as an anode, electrochemically etching and de-alloying to obtain nanoporous copper; introducing a carbon source, and uniformly growing graphene on the surface of the nanoporous copper, and hot pressing and sintering densification to obtain a graphene / copper composite material. Although the graphene / copper nanocomposite material of the invention has high strength and conductivity, it does not study the material's antioxidant properties and thermal expansion properties.
[0008] Therefore, in view of the above-mentioned deficiencies in the prior art, it is of great significance to find a graphene copper material for semiconductor bonding wire with excellent oxidation resistance and electrical conductivity and low thermal expansion coefficient and a preparation method thereof. Summary of the invention
[0009] The object of the present invention is to provide a graphene copper alloy and a preparation method and application thereof. The graphene copper alloy has a low thermal expansion coefficient, high oxidation resistance, strength and electrical conductivity, and is very suitable for the preparation of bonding wires.
[0010] The first aspect of the present invention provides a graphene copper alloy, comprising the following components in percentage by mass: 0.01-0.2% graphene, O≤5ppm, impurity content≤0.001%, and the balance is copper, wherein the number of graphene layers is less than 10.
[0011] The present invention controls the content and number of graphene layers and the oxygen content in the graphene copper alloy to ensure a good bonding interface between the graphene and the substrate and avoid graphene agglomeration, so that the graphene copper alloy has a low thermal expansion coefficient, excellent oxidation resistance, electrical conductivity and mechanical properties.
[0012] Graphene is the most effective reinforcing filling material for manufacturing composite materials. Its reinforcing mechanism mainly lies in the unique structural characteristics of graphene and the formation of a good bonding interface with the matrix. Therefore, in order to obtain good comprehensive properties such as conductivity and mechanics, the graphene content must be greater than 0.01%. However, due to the great difference in density between graphene and the metal matrix, the interface wettability between the two is extremely poor. Once the graphene content exceeds 0.2%, it is easy to form agglomeration between graphene, which becomes a crack source, but causes the graphene copper material to become embrittled, and the back road cannot be processed. Preferably, in the graphene copper alloy, the content of graphene is 0.05-0.1%.
[0013] Oxygen elements will replace carbon atoms in the graphene benzene ring at high temperatures, destroying the two-dimensional structure of graphene and further causing graphene to aggregate. The present invention controls the oxygen content in the graphene copper alloy to be below 5 ppm to avoid the occurrence of graphene agglomeration. More preferably, the oxygen content in the graphene copper alloy is controlled to be below 3 ppm.
[0014] The number of graphene layers is an important factor affecting graphene copper composite materials. As the number of graphene layers increases, the characteristics of graphene as a two-dimensional planar material will gradually be broken, and the high conductivity, good mechanical properties and other properties will be lost. At the same time, as a two-dimensional planar material, when graphene is heated, the two-dimensional expansion coefficient is small, and even when heated at low temperatures, the thermal expansion coefficient is negative. However, when the number of graphene layers increases, due to the anisotropy of graphene, its expansion coefficient decreases significantly, and even produces positive expansion.
[0015] Preferably, in the graphene copper alloy, the number of graphene layers is less than 5 layers. Further preferably, the number of graphene layers is less than 5 layers, and the number of graphene layers less than 3 layers accounts for more than 60% of the total number of graphene. The present invention controls the number of graphene layers within the above range to obtain a graphene copper alloy with better oxidation resistance, electrical conductivity and mechanical properties and lower thermal expansion coefficient. More preferably, the number of graphene layers is controlled to be less than 3 layers.
[0016] Preferably, in the graphene copper alloy, the graphene is distributed in a 3D mesh form, and the copper particles are wrapped in the 3D mesh structure of the graphene. The graphene of the present invention wraps the copper particles in a mesh form in the copper matrix, and the mesh graphene isolates and divides the copper matrix. Only after the outer layer of graphene is corroded will the copper matrix be further corroded, so its anti-oxidation performance is greatly improved.
[0017] Preferably, the graphene copper alloy has a tensile strength of ≥280 MPa, an elongation of ≥30%, a conductivity of ≥70% IACS, a weight loss rate of <2%, and a thermal expansion coefficient of ≤17.3×10 -6 / ℃.
[0018] The second aspect of the present invention provides a method for preparing the graphene copper alloy, comprising the following steps: batching → melting → casting → extrusion → coil drawing → online non-contact annealing → continuous drawing and annealing;
[0019] Wherein, in the batching process, raw materials meeting the requirements are prepared according to the proportion, and the raw materials include pure copper, copper-graphene intermediate master alloy and cored wire, wherein the cored wire is obtained by wrapping the copper-graphene intermediate master alloy with a copper strip;
[0020] In the casting process, pure copper is melted into molten copper and enters a chute containing a copper-graphene intermediate master alloy, the copper-graphene intermediate master alloy is melted, the melted copper-graphene intermediate master alloy is evenly mixed with the molten copper and then enters a crystallizer, where it is stirred for casting, and at the same time, a cored wire is fed into the chute according to the casting speed.
[0021] Due to the complete non-wettability of the interface between graphene and copper matrix, if graphene is directly added to copper water, it is basically impossible to achieve the interface bonding between graphene and copper. Moreover, due to the large difference in specific gravity between copper and graphene, direct addition will lead to severe segregation. Therefore, it is necessary to make graphene and copper into an intermediate alloy and add them in the form of an intermediate alloy to improve the wettability of the interface between graphene and copper, ensure that the intermediate alloy is evenly dispersed in the copper water after melting, so as to form a good bonding interface between graphene and the matrix, and then prepare a graphene copper alloy with excellent performance.
[0022] Preferably, in the copper-graphene intermediate master alloy, the content of graphene is 3-5wt%, and the number of graphene layers is less than 10 layers, preferably less than 5 layers, and more preferably less than 3 layers, and the number of graphene layers accounts for more than 60% of the total number of graphene.
[0023] Preferably, the copper-graphene master alloy is in granular form, with a particle size not exceeding 1 cm. When the particle size is too large, the gaps between particles in the cored wire are large, the density of the cored wire is insufficient, and the composition is easily unstable. In addition, if the master alloy particles are too large, unmelted particles are likely to enter the ingot, resulting in cracking during subsequent processing.
[0024] Preferably, the cored wire has a diameter of 5-10 cm. If the cored wire diameter exceeds 10 cm, the cored wire addition speed is slow, and speed fluctuation has a greater impact on the composition. If the cored wire diameter is less than 5 cm, the addition speed is fast, and some parts do not have time to melt, and the temperature at the cored wire addition position drops too quickly, resulting in uneven composition.
[0025] Preferably, in the copper-graphene intermediate master alloy, copper particles are coated in graphene. The preparation method of the copper-graphene intermediate master alloy is as follows:
[0026] (1) Grinding the copper powder and graphene that meet the requirements according to the ratio, first adding all the graphene and 1 / 4-1 / 2 of the copper powder, and grinding for the first time. After the grinding is completed, adding the remaining copper powder, and grinding for the second time to obtain a mixed powder;
[0027] (2) hot pressing the mixed powder obtained in step (1), and then crushing the resulting billet to obtain the copper-graphene intermediate master alloy.
[0028] The present invention adopts two grindings, and in the first grinding, the copper powder surface is ensured to be completely coated with graphene, and in combination with the second ball milling, the copper powder and the graphene are fully mixed. The master alloy of graphene-coated copper particles can be prepared by the above method, and then the graphene copper alloy of graphene-coated copper particles can be prepared subsequently, thereby improving the oxidation resistance of the graphene copper alloy.
[0029] Preferably, in step (1), the particle size of the copper powder is 0.5-20 microns, more preferably 0.5-5 microns; the particle size of the graphene is 10-200 nanometers, more preferably 10-50 nanometers, and the number of graphene layers is required to be 1-10 layers, preferably 1-5 layers, and more preferably 1-3 layers, exceeding 60%.
[0030] Preferably, in step (2), during the first grinding, the grinding machine speed is 500-2000 r / min, and the grinding time is 60-300 minutes; during the second grinding, the grinding machine speed is 500-2000 r / min, and the ball milling time is 120-600 minutes.
[0031] Preferably, in step (2), 1 / 3 of the total copper powder is added for grinding during the first grinding.
[0032] Preferably, in step (3), the hot pressing temperature is 600-800° C., the hot pressing specification is φ20-60 mm, and then the hot-rolled billet is crushed to obtain the copper-graphene intermediate master alloy.
[0033] Preferably, in the melting process, a copper raw material with a purity greater than 99.995% is added to a smelting furnace, the temperature is increased for melting, and calcined charcoal is added during the heating process. After the electrolytic plate is melted, the temperature is maintained at 1100-1150°C, the charcoal covering thickness is greater than 20 cm, and at the same time, a mixed gas of carbon monoxide and argon is blown through a bottom blowing device for degassing and deoxidation, and the deoxidation time is not less than 60 minutes; after the deoxidation is completed, a gas protection cover is covered, a protective gas is introduced, and the furnace temperature is increased to 1200-1300°C.
[0034] Preferably, in the casting process, the mass of the molten copper is m1, the mass of the copper-graphene intermediate master alloy is m2, and m1 and m2 satisfy: m2= m1×a / b, wherein a is the mass content of graphene in the finished product, and b is the mass content of graphene in the copper-graphene intermediate master alloy;
[0035] The loosening speed of the core wire during casting is V1, V1=D 2 / d 2×V0×a / b×C; wherein a is the mass content of graphene in the finished product, b is the mass content of graphene in the copper-graphene intermediate master alloy, D is the specification of the drawing ingot, d is the diameter of the cored wire, V0 is the casting speed, and C is the compensation coefficient, which is between 1.2 and 1.5.
[0036] During the casting process, a certain weight of molten copper is first transferred into the chute. According to the weight of the molten copper and the requirements of the finished product composition, a certain amount of copper-graphene intermediate master alloy is placed in the chute in advance (to ensure the composition, the amount of intermediate alloy is generally placed according to the upper limit of the composition). When the molten copper in the chute reaches a certain weight, the stopper of the chute is opened to allow the molten copper to enter the crystallizer and start casting. At this time, molten copper is continuously transferred from the melting furnace to the chute, and the amount of molten copper transferred is consistent with the ingot cast from the crystallizer. Therefore, the weight and composition requirements of the transferred molten copper can be calculated according to the casting speed, the weight of the graphene intermediate alloy that needs to be supplemented can be calculated, and the speed of adding the cored wire can be calculated based on this.
[0037] The present invention enables the casting process to be carried out continuously through the casting process, thereby improving production efficiency, and can accurately control the composition of the ingot, thereby ensuring the uniformity and consistency of the ingot and improving the overall quality of the product.
[0038] Preferably, in the casting process, the stirring is electromagnetic stirring, the electromagnetic stirring frequency is controlled at 3-10 Hz, and the electromagnetic stirring current is controlled at 80-120 A. The present invention prevents graphene agglomeration by electromagnetic stirring; however, the electromagnetic stirring frequency cannot be too large, otherwise the electromagnetic stirring force decays too quickly, the stirring force of graphene copper at the center and edge of the crystallizer is inconsistent, and stratification is easy.
[0039] Preferably, in the extrusion process, the extrusion temperature is controlled at 750-850° C. If the temperature is too high, the graphene structure will be destroyed under the action of the high-temperature extrusion force, and if the temperature is too low, the extrusion will not work.
[0040] Preferably, in the disk pulling process, the total disk pulling processing rate is not less than 70% and not more than 90%, and the single pass processing rate does not exceed 30%. Controlling the disk pulling process within this range can ensure sufficient work hardening (producing sufficient recrystallization driving force) without generating cracks at the graphene position.
[0041] Preferably, in the online non-contact annealing process, the annealing temperature is 600-800°C, the annealing speed is 0.5-0.8 m / min, and the annealing atmosphere is an inert gas. The present invention adopts an online non-contact method, and through recrystallization at high temperature, the copper matrix around the graphene undergoes recrystallization, further increasing the interface bonding strength between the matrix and the graphene copper.
[0042] Preferably, in the continuous drawing and annealing process, the wire drawing speed of the large wire drawing is 400-600 m / min, and the annealing voltage is 6-8 V; the wire drawing speed of the medium wire drawing is 500-800 m / min, and the annealing voltage is 7-9 V; the wire drawing speed of the small wire drawing is 800-1000 m / min, and the annealing voltage is 8-10 V; the wire drawing speed of the micro wire drawing is 900-1100 m / min, and the annealing voltage is 10-12 V. After the disk drawing and online non-contact annealing, the graphene greatly increases the strength of the material, so the wire drawing speed cannot be too fast, otherwise it is easy to break. At the same time, due to the enhanced conductivity, the annealing voltage is reduced to ensure that the annealing is not over-burned.
[0043] Preferably, the graphene copper alloy is graphene copper wire.
[0044] The third aspect of the present invention provides the use of the graphene copper wire in preparing bonding wires. The graphene copper wire of the present invention has a low thermal expansion coefficient, high oxidation resistance, strength and conductivity, and can be widely used in the preparation of bonding wires.
[0045] Compared with the prior art, the present invention has the following beneficial technical effects:
[0046] (1) The present invention controls the quantity and morphological distribution of graphene, and at the same time cooperates with the synergistic effect of casting and processing heat treatment to ensure that a good bonding interface is formed between graphene and the copper matrix, so that it has excellent oxidation resistance, low thermal expansion coefficient, and good mechanical and electrical properties. Compared with ordinary oxygen-free copper, the graphene copper alloy prepared by the present invention has improved strength and conductivity by 5%-10%, oxidation resistance by 10%-15%, and a lower thermal expansion coefficient, and has broad application prospects in the preparation of bonding wires;
[0047] (2) The present invention prepares graphene and copper into an intermediate alloy, and adds them in the form of an intermediate alloy to improve the wettability of the interface between graphene and copper, and ensures that the intermediate alloy is evenly dispersed in the copper water after melting, so that a good bonding interface is formed between the graphene and the substrate, thereby preparing a graphene copper alloy with excellent performance;
[0048] (3) The present invention develops a method for preparing a copper-graphene intermediate master alloy. The method can be used to obtain an intermediate master alloy of graphene-coated copper particles, thereby enabling the subsequent preparation of a graphene-copper alloy of graphene-coated copper particles, thereby improving the oxidation resistance of the graphene-copper alloy;
[0049] (4) The casting process of the present invention enables the casting process to be carried out continuously, thereby improving production efficiency, and can accurately control the composition of the ingot, thereby ensuring the uniformity and consistency of the ingot and improving the overall quality of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] Figure 1 This is a transmission electron microscope photograph of graphene extracted after full corrosion of the graphene copper wire in Example 1 of the present invention. DETAILED DESCRIPTION
[0051] The present invention is further described in detail below with reference to the accompanying drawings.
[0052] The present invention provides three embodiments and one comparative example, and the specific components are shown in Table 1. Embodiment The method of the present invention is used to prepare semiconductor bonding wire graphene copper wire.
[0053] The copper-graphene intermediate master alloy of the present invention is prepared by the following method:
[0054] 1) Raw materials: preferably, the electrolytic copper powder has a particle size of 0.5-20 microns, more preferably 0.5-5 microns, the graphene particle size is 10-200 nanometers, more preferably 10-50 nanometers, and the number of graphene layers is required to be 1-10 layers, preferably 1-5 layers, more preferably 1-3 layers, with the number exceeding 60%;
[0055] 2) Ball milling: First, add all the graphene to the ball mill. In the first ball milling, add 1 / 3 of the copper powder in the ingredients. The ball mill speed is 500-2000r / min and the ball milling time is 60-300 minutes. After the ball milling, add all the remaining copper powder. The ball mill speed is 500-2000r / min and the ball milling time is 120-600 minutes. In the first ball milling, ensure that the surface of the copper powder is completely covered with graphene. Combined with the second ball milling, let the copper powder and graphene be fully mixed;
[0056] 3) Hot pressing: The mixed powder is hot pressed at a temperature of 600-800°C and a specification of φ20-60mm, and then the hot-rolled billet is crushed into a copper-graphene intermediate master alloy of a desired particle size.
[0057] Specifically, when preparing the copper-graphene intermediate master alloy in Example 1 of the present invention, the particle size of the electrolytic copper powder is 0.5-10 microns, the number of graphene layers is 5 or less, and the number of graphene layers below 3 is more than 80%. During the first ball milling, 1 / 3 of the copper powder is added, the ball mill speed is 500r / min, and the ball milling time is 300min; during the second ball milling, the ball mill speed is 1500r / min, the ball milling time is 300min, the hot pressing temperature is 700°C, and the hot pressing specification is 50mm.
[0058] When preparing the copper-graphene intermediate master alloy in Example 2 of the present invention, the particle size of the electrolytic copper powder is 1-15 microns, the number of graphene layers is 5 or less, and the number of graphene layers below 3 is more than 90%. During the first ball milling, 1 / 4 of the copper powder is added, the ball mill speed is 2000r / min, and the ball milling time is 60min; during the second ball milling, the ball mill speed is 2000r / min, the ball milling time is 120min, the hot pressing temperature is 600°C, and the hot pressing specification is 60mm.
[0059] When preparing the copper-graphene intermediate master alloy in Example 3 of the present invention, the particle size of the electrolytic copper powder is 0.5-5 microns, the number of graphene layers is 5 or less, and the number of graphene layers below 3 is more than 80%. During the first ball milling, 1 / 2 of the copper powder is added, the ball mill speed is 1500r / min, and the ball milling time is 80min; during the second ball milling, the ball mill speed is 1000r / min, the ball milling time is 150min, the hot pressing temperature is 800°C, and the hot pressing specification is 20mm.
[0060] Example 1 Preparation of 0.05% graphene content φ0.05 mm graphene copper wire
[0061] 1) Ingredients: Ingredients are prepared according to the required ingredients, wherein graphene is added in the form of a copper-graphene intermediate master alloy, the graphene content in the copper-graphene intermediate master alloy is 4wt%, the number of graphene layers is less than 5 layers, and the total number of graphene layers less than 3 layers exceeds 80%; the copper-graphene intermediate master alloy is granular, and the particle size does not exceed 1cm; the master alloy particles are wrapped with high-purity oxygen-free copper strips to form a cored wire, and the diameter of the cored wire is 8cm; the remaining ingredients use high-purity electrolytic plates, and the copper content in the electrolytic plates is greater than 99.995%;
[0062] 2) Melting: First, add the electrolytic plate into the smelting furnace, heat it up and melt it, add calcined charcoal during the heating process, after the electrolytic plate is melted, the temperature is maintained at 1100-1130℃, and the charcoal is covered with a thickness of 20cm. At the same time, a mixed gas of carbon monoxide and argon is blown through the bottom blowing device for degassing and deoxidation, wherein the proportion of carbon monoxide is 20%, and the deoxidation time is not less than 60min; after the deoxidation is completed, cover the gas protection cover, and introduce the protective gas, which is argon, and at the same time increase the furnace temperature to 1250-1300℃;
[0063] 3) Electromagnetic casting: open the drain plug rod, the molten copper enters the chute with gas protection, when the molten copper in the chute is 150-200kg, 2.5kg of copper-graphene intermediate master alloy has been placed in the chute in advance, open the drain plug rod of the chute, the molten copper in the chute enters the crystallizer with electromagnetic stirring, when the molten copper in the crystallizer is 2cm away from the upper edge of the crystallizer, start the electromagnetic stirring, the electromagnetic stirring frequency is 5Hz, the stirring current is 100A, at the same time, start the casting machine, the casting speed is 60mm / min, the diameter of the pull casting ingot is 250mm, and the graphene copper cored wire is fed into the chute at the same time, and the cored wire feeding speed is 0.9m / min; there is a protective gas hood above the crystallizer, and the protective atmosphere is argon;
[0064] 4) Extrusion: The electromagnetically cast ingot is hot extruded into round bars with a specification of φ30mm;
[0065] 5) Coil drawing: Through coil drawing, the extruded round rod is drawn to φ15mm;
[0066] 6) Online non-contact annealing: Through non-contact annealing, the interface bonding between graphene and copper substrate is further strengthened. The annealing temperature is 800°C and the annealing speed is 0.7m / min.
[0067] 7) Continuous drawing and annealing: The graphene copper is drawn to the finished product specifications by continuous drawing and annealing. The large drawing speed is 450-500m / min, the annealing voltage is 6.8-7.2V, the medium drawing speed is 650-700m / min, the annealing voltage is 7.0-8.0V, the small drawing speed is 800-1000m / min, the annealing voltage is 8.0-9.5V, and the micro drawing speed is 900-1100m / min, and the annealing voltage is 9.0-11.0V;
[0068] 8) Finished product testing: Conduct electrical conductivity, corrosion resistance, and thermal expansion coefficient tests on finished products.
[0069] Example 2 Preparation of 0.01% graphene content φ0.03 mm graphene copper wire
[0070] 1) Ingredients: Ingredients are prepared according to the required ingredients, and graphene is added in the form of copper-graphene intermediate master alloy, the graphene content in the copper-graphene intermediate master alloy is 3wt%, the number of graphene layers is less than 5 layers, and the total number of graphene layers less than 3 layers exceeds 90%; the copper-graphene intermediate master alloy is granular, and the particle size does not exceed 1cm; the master alloy particles are wrapped with high-purity oxygen-free copper strips to form a cored wire, and the diameter of the cored wire is 8cm; the remaining ingredients use high-purity electrolytic plates, and the copper content in the electrolytic plates is greater than 99.995%;
[0071] 2) Melting: First, add the electrolytic plate into the smelting furnace, heat it up and melt it, add calcined charcoal during the heating process, after the electrolytic plate is melted, the temperature is maintained at 1100-1150℃, and the charcoal covers the thickness of 20cm. At the same time, a mixed gas of carbon monoxide and argon is blown through the bottom blowing device for degassing and deoxidation, wherein the proportion of carbon monoxide is 15%, and the deoxidation time is not less than 60min; after the deoxidation is completed, cover the gas protection cover, and introduce the protective gas, which is argon, and at the same time increase the furnace temperature to 1200-1300℃;
[0072] 3) Electromagnetic casting: open the drain plug rod, the molten copper enters the chute with gas protection, when the molten copper in the chute is 150-200kg, 2.0kg of copper-graphene intermediate master alloy has been placed in the chute in advance, open the drain plug rod of the chute, the molten copper in the chute enters the crystallizer with electromagnetic stirring, when the molten copper in the crystallizer is 2cm away from the upper edge of the crystallizer, start the electromagnetic stirring, the electromagnetic stirring frequency is 5Hz, the stirring current is 100A, at the same time, start the casting machine, the casting speed is 70mm / min, the diameter of the pull casting ingot is 250mm, and the graphene copper cored wire is fed into the chute at the same time, and the cored wire feeding speed is 0.85m / min; there is a protective gas hood above the crystallizer, and the protective atmosphere is argon;
[0073] 4) Extrusion: The electromagnetically cast ingot is hot extruded into round bars with a specification of φ30mm;
[0074] 5) Coil drawing: Through coil drawing, the extruded round rod is drawn to φ12mm;
[0075] 6) Online non-contact annealing: Through non-contact annealing, the interface bonding between graphene and copper substrate is further strengthened. The annealing temperature is 750°C and the annealing speed is 0.75m / min.
[0076] 7) Continuous drawing and annealing: The graphene copper is drawn to the finished product specifications by continuous drawing and annealing. The large drawing speed is 500-550m / min, the annealing voltage is 7.2-8.0V, the medium drawing speed is 750-800m / min, the annealing voltage is 7.5-9.0V, the small drawing speed is 900-1100m / min, the annealing voltage is 9.0-10.5V, the micro drawing speed is 1100-1200m / min, and the annealing voltage is 10.0-11.0V;
[0077] 8) Finished product testing: Conduct electrical conductivity, corrosion resistance, and thermal expansion coefficient tests on finished products.
[0078] Example 3 Preparation of 0.08% graphene content φ0.04 mm graphene copper wire
[0079] 1) Ingredients: Ingredients are prepared according to the required ingredients, and graphene is added in the form of copper-graphene intermediate master alloy, the graphene content in the copper-graphene intermediate master alloy is 5wt%, the number of graphene layers is less than 5 layers, and the total number of graphene layers less than 3 layers exceeds 80%; the copper-graphene intermediate master alloy is granular, and the particle size does not exceed 1cm; the master alloy particles are wrapped with high-purity oxygen-free copper strips to form a cored wire, and the diameter of the cored wire is 8cm; the remaining ingredients use high-purity electrolytic plates, and the copper content in the electrolytic plates is greater than 99.995%;
[0080] 2) Melting: First, add the electrolytic plate into the smelting furnace, heat it up and melt it, add calcined charcoal during the heating process, after the electrolytic plate is melted, the temperature is maintained at 1100-1150℃, and the charcoal covers the thickness of 20cm. At the same time, a mixed gas of carbon monoxide and argon is blown through the bottom blowing device for degassing and deoxidation, wherein the proportion of carbon monoxide is 30%, and the deoxidation time is not less than 60min; after the deoxidation is completed, cover the gas protection cover, and introduce the protective gas, which is argon, and at the same time increase the furnace temperature to 1200-1300℃;
[0081] 3) Electromagnetic casting: open the drain plug rod, the molten copper enters the chute with gas protection, when the molten copper in the chute is 150-200kg, 3.2g of copper-graphene intermediate master alloy has been placed in the chute in advance, open the drain plug rod of the chute, the molten copper in the chute enters the crystallizer with electromagnetic stirring, when the molten copper in the crystallizer is 2cm away from the upper edge of the crystallizer, start the electromagnetic stirring, the electromagnetic stirring frequency is 3Hz, the stirring current is 120A, at the same time, start the casting machine, the casting speed is 65mm / min, the diameter of the pull casting ingot is 250mm, and the graphene copper cored wire is fed into the chute at the same time, and the cored wire feeding speed is 1.2m / min; there is a protective gas hood above the crystallizer, and the protective atmosphere is argon;
[0082] 4) Extrusion: The electromagnetically cast ingot is hot extruded into round bars with a specification of φ28mm;
[0083] 5) Coil drawing: Through coil drawing, the extruded round rod is drawn to φ13mm;
[0084] 6) Online non-contact annealing: Through non-contact annealing, the interface bonding between graphene and copper substrate is further strengthened. The annealing temperature is 800°C and the annealing speed is 0.6m / min.
[0085] 7) Continuous drawing and annealing: The graphene copper is drawn to the finished product specifications by continuous drawing and annealing. The large drawing speed is 400-450m / min, the annealing voltage is 6.5-7.0V, the medium drawing speed is 600-750m / min, the annealing voltage is 6.5-7.5V, the small drawing speed is 700-900m / min, the annealing voltage is 7.5-8.5V, the micro drawing speed is 850-1000m / min, and the annealing voltage is 9.0-10.0V;
[0086] 8) Finished product testing: Conduct electrical conductivity, corrosion resistance, and thermal expansion coefficient tests on finished products.
[0087] Comparative Example 1 is oxygen-free copper wire
[0088] 1) Ingredients: Ingredients are prepared according to the required ingredients, and the copper content in the electrolytic plate is above 99.95%;
[0089] 2) Melting: First, add the electrolytic plate into the smelting furnace, heat it up and melt it, add calcined charcoal during the heating process, after the electrolytic plate is melted, the temperature is maintained at 1100-1150℃, and the charcoal covers the thickness of 20cm. At the same time, a mixed gas of carbon monoxide and argon is blown through the bottom blowing device for degassing and deoxidation, wherein the proportion of carbon monoxide is 15%, and the deoxidation time is not less than 60min; after the deoxidation is completed, cover the gas protection cover, and introduce the protective gas, which is argon, and at the same time increase the furnace temperature to 1200-1300℃;
[0090] 3) Electromagnetic casting: open the drain plug rod, the molten copper enters the chute with gas protection, when the molten copper in the chute is 150-200kg, open the drain plug rod of the chute, the molten copper in the chute enters the crystallizer with electromagnetic stirring, when the molten copper in the crystallizer is 2cm away from the upper edge of the crystallizer, start the electromagnetic stirring, the electromagnetic stirring frequency is 5Hz, the stirring current is 100A, at the same time, start the casting machine, the casting speed is 65mm / min, the diameter of the pull casting ingot is 250mm, there is a protective gas cover above the crystallizer, and the protective atmosphere is argon;
[0091] 4) Extrusion: The electromagnetically cast ingot is hot extruded into round bars with a specification of φ28mm;
[0092] 5) Coil drawing: Through coil drawing, the extruded round rod is drawn to φ12mm;
[0093] 6) Online non-contact annealing: Through non-contact annealing, the annealing temperature is 750°C and the annealing speed is 0.7m / min;
[0094] 7) Continuous drawing and annealing: The oxygen-free copper is drawn to the finished product specifications by continuous drawing and annealing. The drawing speed of the large drawing is 600-700m / min, the annealing voltage is 7.5-9.0V, the drawing speed of the medium drawing is 800-1000m / min, the annealing voltage is 9.0-10.0V, the drawing speed of the small drawing is 1100-1300m / min, the annealing voltage is 9.5-11.5V, and the drawing speed of the micro drawing is 1200-1400m / min, and the annealing voltage is 11.0-13.0V;
[0095] 8) Finished product testing: Conduct electrical conductivity, corrosion resistance, and thermal expansion coefficient tests on finished products.
[0096] The performance of the embodiments and comparative examples was tested, and the test data are shown in Table 1.
[0097] Table 1 Performance test results of graphene copper wires of embodiments and comparative examples
[0098] Conductivity test: Place the conductivity test device (bridge) in a protective gas oven, raise the temperature to 150°C, keep it warm for 2 hours, and then measure the conductivity of the conductor.
[0099] The corrosion resistance is tested in accordance with the neutral salt spray test of GB / T 10125-2012 “Salt spray test for metallic materials and coatings”. The test time is 48 hours, and the weight loss rate before and after corrosion is measured.
[0100] Thermal expansion coefficient test: Tested in accordance with GB / T 4339-2008 "Determination of characteristic parameters of thermal expansion of metallic materials".
Claims
1. A graphene copper alloy, characterized in that: The invention comprises the following components in percentage by mass: 0.01-0.2% graphene, O≤5ppm, impurity content≤0.001%, and the balance is copper, wherein the number of graphene layers in the graphene copper alloy is less than 5, and the number of graphene layers less than 3 accounts for more than 60% of the total number of graphene, the graphene is distributed in a 3D mesh shape, and the copper particles are wrapped in the 3D mesh structure of the graphene; the tensile strength of the graphene copper alloy is ≥280MPa, the elongation is ≥30%, the conductivity is ≥70%IACS, the weight loss rate is <2%, and the thermal expansion coefficient is ≤17.3×10 -6 / ℃.
2. The method for preparing the graphene copper alloy according to claim 1, characterized in that: The process includes the following steps: batching → melting → casting → extrusion → coil drawing → online non-contact annealing → continuous drawing and annealing; Wherein, in the batching process, raw materials meeting the requirements are prepared according to the proportion, and the raw materials include pure copper, copper-graphene intermediate master alloy and cored wire, wherein the cored wire is obtained by wrapping the copper-graphene intermediate master alloy with a copper strip; In the casting process, pure copper is melted into molten copper and enters a chute containing a copper-graphene intermediate master alloy, the copper-graphene intermediate master alloy is melted, the melted copper-graphene intermediate master alloy is evenly mixed with the molten copper and then enters a crystallizer, where it is stirred for casting, and at the same time, a cored wire is fed into the chute according to the casting speed.
3. The preparation method according to claim 2, characterized in that: In the copper-graphene intermediate master alloy, the content of graphene is 3-5wt%.
4. The preparation method according to claim 2, characterized in that: The copper-graphene intermediate master alloy is in granular form, with a particle size not exceeding 1 cm; the diameter of the cored wire is 5-10 cm.
5. The preparation method according to claim 2, characterized in that: In the copper-graphene intermediate master alloy, copper particles are coated in graphene.
6. The preparation method according to claim 2, characterized in that: The method for preparing the copper-graphene intermediate master alloy comprises the following steps: (1) Grinding the copper powder and graphene that meet the requirements according to the ratio, first adding all the graphene and 1 / 4-1 / 2 of the copper powder, and grinding for the first time. After the grinding is completed, adding the remaining copper powder, and grinding for the second time to obtain a mixed powder; (2) hot pressing the mixed powder obtained in step (1), and then crushing the resulting billet to obtain the copper-graphene intermediate master alloy.
7. The preparation method according to claim 6, characterized in that: The particle size of the copper powder is 0.5-20 μm.
8. The preparation method according to claim 6, characterized in that: During the first grinding, the grinding machine speed is 500-2000r / min, and the grinding time is 60-300 minutes; during the second grinding, the ball mill speed is 500-2000r / min, and the grinding time is 120-600 minutes.
9. The preparation method according to claim 6, characterized in that: The hot pressing temperature is 600-800°C.
10. The preparation method according to claim 2, characterized in that: In the casting process, the mass of the molten copper is m1, the mass of the copper-graphene intermediate master alloy is m2, and m1 and m2 satisfy: m2= m1×a / b, where a is the mass content of graphene in the finished product, and b is the mass content of graphene in the copper-graphene intermediate master alloy; The loosening speed of the core wire during casting is V1, V1=D 2 / d 2 ×V0×a / b×C; where D is the specification of the pull casting ingot, d is the diameter of the cored wire, V0 is the casting speed, and C is the compensation coefficient, which is between 1.2-1.
5.
11. The preparation method according to claim 2, characterized in that: In the casting process, the stirring is electromagnetic stirring, the electromagnetic stirring frequency is controlled at 3-10 Hz, and the electromagnetic stirring current is controlled at 80-120A.
12. The preparation method according to claim 2, characterized in that: In the disc-pulling process, the total disc-pulling processing rate is not less than 70% and not more than 90%, and the single-pass processing rate does not exceed 30%.
13. The preparation method according to claim 2, characterized in that: In the online non-contact annealing process, the annealing temperature is 600-800° C., the annealing speed is 0.5-0.8 m / min, and the annealing atmosphere is an inert gas.
14. The preparation method according to claim 2, characterized in that: In the continuous drawing and annealing process, the large drawing speed is 400-600 m / min, and the annealing voltage is 6-8 V; the medium drawing speed is 500-800 m / min, and the annealing voltage is 7-9 V; the small drawing speed is 800-1000 m / min, and the annealing voltage is 8-10 V; The micro-drawing speed is 900-1100m / min, and the annealing voltage is 10-12V.
15. The graphene copper alloy according to claim 1, characterized in that: The graphene copper alloy is graphene copper wire.
16. Use of the graphene copper wire according to claim 15 in preparing bonding wires.
Citation Information
Patent Citations
Copper microalloy bonding wire and preparation method thereof
CN107195608A
High strength, high conductivity graphene / copper nanocomposite material and preparation method and application thereof
CN108149046A
High-strength and high-conductivity graphene copper composite wire and preparation method thereof
CN112359244A
Copper alloy bar and preparation method thereof
CN116179889A